Mega-Predators of the past [book with audioplayer] - Stewart, Melissa ([Library Ideas, LLC], 2022)
"It is time for T. rex and his dinosaur cousins to step aside and let other mega-predators like the terror bird and the giant ripper lizard take the spotlight! Travel back to prehistoric times and meet some of the most impressive creatures to ever roam the Earth. You'll be amazed at the size and the fierceness of these lesser-known predators, many of them ancient ancestors of animals that we still see today. tewart's cheeky, humorous voice--along with a comical version of the familiar "comparison man"--put these creatures in perspective. Artist and former zoologist Howard Gray brings these predators (back) to life with dynamic, humorous, and scientifically accurate illustrations. Sidebars and extensive back matter material provide more detailed information and context."-- Amazon.